Case Study: The Developing Moral and Transparency in the Operations of the Faculty of Management Science, Suan Sunandha Rajabhat University - Chanwichian, Jeerabhan; Sangjumnong, Manop; Chansongpol, Thanyanant (Arts of Management Journal, 2024)
Results of the case study of the prototype of morality and transparency development in the operation of the Faculty of Management Science, Suan Sunandha Rajabhat University. The objective is to develop knowledge for personnel and understand the problems and guidelines for developing the results of the assessment of morality and transparency in the operation of Suan Sunandha Rajabhat University. By setting the framework in the form of a trial operation specifically for the Faculty of Management Science and selecting 4 issues of the ITA assessment criteria, namely: (1) “The agency can communicate, answer questions, or provide explanations to service recipients”, (2) “the better than before of performance or staff’s services”, and (3) “the methods and procedures of the operation or service are more convenient and faster than before.” And (4) “The agency better opens up opportunities for outsiders to participate in improving and developing the operation.”. A study using the action research method through the project “Workshop on the Development of Morality and Transparency in the Operation of Government Agencies, Faculty of Management Science, Suan Sunandha Rajabhat University.” The results of the knowledge assessment of the project participants, 69 people, increased from the pre-test to 74.42 percent and the post-test to 92.10 percent, and the qualitative study can conclude the results according to the 4 study objectives from the participants who jointly exchanged knowledge, from the perspective of the problem, from the performance of duties, brainstormed to analyze the problems from the operation through the Fishbone diagram, and presented the guidelines for better development of the faculty.